Management Style of Chinese Business Owners in the Chiang Rai Province of Thailand - Walsh, John; Anantarangsi, Sittichai (The South East Asian Journal of Management, 2009)
New challenges face Thailand's economy as it exits the factory age and struggles towards higher value-added economic activities. One important component of new economic development will be encouraging more foreign investment, particularly in the provinces of the country away from Bangkok. China is becoming an increasingly important investment and trade partner for Thailand and the creation of an industrial estate in the northern province of Chiang Rai is in part intended to encourage additional Chinese investment in the country. However, providing space alone is insufficient to understand the need of investors, including their current and future demand for skilled labour. This paper reports on a program of qualitative research featuring in depth interviews of Chinese business-owners and relevant government officials and others aimed at understanding the style and nature of management among Chinese business owners and, hence, to make preparations for future labour market requirements.